Vocational Education and Economic Development in Anaocha Local Government Area of Anambra State: Challenges and Prospects - Elekwa, Josephine Ebere; Moneme, Uju Esther (International Journal on Integrated Education, 2022)
This explained how vocational education will help in creating jobs in Anaocha Local Government Area of Anambra State. The study adopted survey research design. three research questions guided the study and three hypotheses were formulated and tested. The population used for this research is twenty-eight thousand, four hundred and fifty (28450) youths in the craft centres and markets across the ten towns that make up the local government area and the sample size of four hundred (400) youths was selected using Yemen’s formula. A questionnaire was structured for data collection- titled “vocational education and youth empowerment Questionnaire” (VEAYEQ). The data collected was analyzed using percentage, mean and standard deviation. The hypotheses were tested at 0.05 significant level using Pearson Product Moment Correlation coefficient. From the results obtained, the researcher concluded that vocational education has helped a lot in curbing unemployment and this in turn has helped in taking a lot of youths off the streets. This study therefore recommended that more youths should be encouraged to go into skill acquisition, trading and farming in order to be self-employed and self-reliant. Parents and teachers should guide the students into discovering their God-given potentials and harness it from very tender age.